STUDI KOMPARATIF SIKAP KEPEDULIAN SISWA TERHADAP LINGKUNGAN ANTARA SEKOLAH ADIWIYATA DENGAN SEKOLAH YANG BELUM ADIWIYATA DI SMPN KOTA PEKANBARU - Delia, Vista; ', Yustina; ', Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this research is to get a description of the Implementation of Adiwiyata Program in the Growth of Student's Attitude to the Environment at SMPN Kota Pekanbaru. This research was conducted in September 2016 until February 2017. The sample in this study were 44 students of grade 8 SMPN 4 Kota Pekanbaru (Adiwiyata school) and 44 students of grade 8 SMPN 14 Kota Pekanbaru (school not yet adiwiyata) chosen by purposive sampling. The data collection instrument used is a closed questionnaire. Closed questionnaire consists of 20 statements that are divided into 4 indicators: Environmental Based Curriculum, Participatory Based Activity, Utilization of School Infrastructure Facility and Commitment in School Environment Maintenance. All closed questionnaire items are valid and reliable. Questionnaire covered student's caring attitude towards the environment through pearson correlation test, where all item of statement declared valid. To test the reliability of questionnaire through alpha test Cronbach's obtained alpha of 0.79. This validity and reliability test is analyzed with SPSS (Statistical Package for Social Studies) version 17.00 for Windows. The collected data were analyzed descriptively. A description of students' awareness toward the environment at adiwiyata school and school is not yet adiwiyata obtained as follows: Attitude attitude of student to environment at school of adiwiyata showed value 2,72 with category "Baik" while attitude of student care to environment in school yet adiwiyata show value 2,29 With the category "Enough" and known Ho refused Ha accepted, and tcount (3,683) ˃ ttable (1,988) or significance (0,000) <0.05. This means that there is a significant difference in the attitude of students' environmental awareness between SMPN 4 Pekanbaru and SMPN 14 Pekanbaru. Thus, the attitude of students 'care towards the environment in adiwiyata school is higher than the students' attitude toward the environment in the school is not yet adiwiyata.Keywords: Comparative Study, Environmental Attitude, Adiwiyata